Effect of Different Calcium Sources and Calcium Intake on Shell Quality and Bone Characteristics of Laying Hens at Sexual Maturity and End of Lay - Koutoulis, K.C.; Kyriazakis, I.; Perry, G.C.; Lewis, P.D. (International Journal of Poultry Science, 2009)
The influence of supplemental calcium given in flour or granular form and calcium intake on bone properties and egg characteristics of brown-egg laying hens was investigated at sexual maturity and at end of lay. Physical and mechanical bone characteristics were determined using 3-point and torsional tests. There was no effect of calcium source on the measured bone characteristics at sexual maturity. Bone breaking strength was positively correlated with both stiffness and total calcium intake. At 72 weeks, birds which had been offered additional calcium of either source exhibited considerably higher bone breaking strength than did control birds. Bone stiffness of birds offered limestone granules was significantly higher than control birds. Regression analysis showed strong relationships between calcium intake, bone stiffness and breaking strength. Shell quality was significantly better for birds consuming limestone in a granular form than for control birds. Shell quality for birds given limestone flour was intermediate between the other two groups. It is concluded that calcium supplementation increases egg quality, mechanical properties of the bone and as a consequence, may be able to reduce the risk of broken bones at the end of laying period. These effects are independent of the form of the supplemented calcium.